Magnetic anisotropy of elongated thin ferromagnetic nano-islands for artificial spin ice arrays - Wysin, Gary M.; Moura-Melo, W. A.; Mol, L. A. S.; Pereira, A. R. (My University, 2012)
The energetics of thin elongated ferromagnetic nano-islands is considered for some different shapes, aspect ratios, and applied magnetic field directions. These nano-island particles are important for artificial spin-ice materials. For low temperature, the magnetic internal energy of an individual particle is evaluated numerically as a function of the direction of a particle’s net magnetization. This leads to estimations of effective anisotropy constants for (1) the easy axis along the particle’s long direction, and (2) the hard axis along the particle’s thin direction. A spin relaxation algorithm together with fast Fourier transform for the demagnetization field is used to solve the micromagnetics problem for a thin system. The magnetic hysteresis is also found. The results indicate some possibilities for controlling the equilibrium and dynamics in spin-ice materials by using different island geometries.
Keywords: Magnetic anisotropy; Magnetic hysteresis; Micromagnetics; Spin-ice; Effective potential